Long-term survival of the cemented Müller CDH stem: a minimum follow-up of 10 years - Salentiny, Yves (Arch Orthop Trauma Surg, 2018)
INTRODUCTION: Total hip arthroplasty in patients with altered anatomy of the hip and femur, such as in congenital dysplasia of the hip, is challenging and often requires specially designed stems. Müller straight stems have shown excellent long-term results; however, long-term data on the analogous cemented Müller CDH stem are still missing. The aim of this study was to analyze long-term survival, identify potential risk factors for aseptic loosening, and analyze radiological outcome of the cemented Müller CDH stems. MATERIALS AND METHODS: Between 01/1985 and 06/2005, 95 Müller CDH stems (Zimmer, Winterthur, Switzerland) made up of 3 different materials were cemented using 2 different bone cements: 38 of stainless steel/high-viscosity cement, 31 of a cobalt-chrome-based alloy (CoCr)/low-viscosity cement, and 26 of a titanium-based alloy (Ti)/low-viscosity cement. All patients had a prospective clinical and radiological follow-up according to the standards of our institution. The cumulative incidence for revision of the stem was calculated using a competing risk model. To identify demographic and implant-related risk factors for aseptic loosening of the stem, a multivariate regression model for competing risks was performed. RESULTS: The cumulative risk of revision at 15 years was 12.5% (95% CI 6.6–20.5%) for aseptic loosening of the stem as endpoint, with marked differences for the various stem materials used: stainless steel 2.7% (0.2–12.3%), CoCr 12.9% (4.0–27.3%), and Ti 24.5% (9.6–43.1%). Regression modeling revealed that Ti stems in combination with low-viscosity cement (HR 10.2) and implantation with an axis deviation greater than 3° (HR 3.8) are risk factors for aseptic loosening. CONCLUSIONS: Long-term survival of the cemented Müller CDH stem is comparable to other Müller-type straight stems and uncemented implants. Similar to the original Ti Müller straight stem, the Ti Müller CDH stem also showed an increased risk for aseptic loosening and should, therefore, no longer be used.